2018
DOI: 10.1177/1078155217753740
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib-induced pulmonary arterial hypertension – A rare late complication

Abstract: Dasatinib is a dual Src/Abl tyrosine kinase inhibitor approved for frontline and second line treatment of chronic phase chronic myelogenous leukemia. Pulmonary arterial hypertension is defined by an increase in mean pulmonary arterial pressure >25 mmHg at rest. Dasatinib-induced pulmonary hypertension has been reported in less than 1% of patients on chronic dasatinib treatment for chronic myelogenous leukemia. The pulmonary arterial hypertension from dasatinib may be categorized as either group 1 (drug-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Another proposed mechanism is related to SRC family kinases and platelet-derived growth factor (PDGF) pathway [54,62,64]. SRC family kinases have a role in smooth muscle cells reproduction and also reducing pulmonary artery tone while their inhibition result in apoptosis and raised vascular resistance.…”
Section: Dasatinib-induced Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another proposed mechanism is related to SRC family kinases and platelet-derived growth factor (PDGF) pathway [54,62,64]. SRC family kinases have a role in smooth muscle cells reproduction and also reducing pulmonary artery tone while their inhibition result in apoptosis and raised vascular resistance.…”
Section: Dasatinib-induced Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Dasatinib-induced PAH predominantly occurs in women and is often concomitant with previous or present PE [ 15 ]. PAH in a CML patient may be drug-induced (group 1) or related to CML pathophysiology [ 15 , 61 - 63 ]. It has been demonstrated that treatment with dasatinib causes a dose-dependent increase in production of mitochondrial ROS; resulting to endothelial apoptosis, pulmonary endothelial dysfunction and pulmonary hypertension.…”
Section: Dasatinibmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, dasatinib also shows higher selectivity and affinity to the BCR/ABL kinase domain than imatinib, and dasatinib can cross the blood-brain barrier to prevent and eradicate central nervous system leukemia. It is used to treat patients with imatinib resistance or relapse while receiving imatinib [8] . According to the Chinese Children's Cancer Group study ALL-2015 (CCCG-ALL-2015), patients treated with dasatinib had significantly higher rates of 4-year EFS (71.0% vs 48.9%) and OS (88.4% vs 69.2%) and lower relapse rates (19.8% vs 34.4%) than the 97 patients treated with imatinib [4] .…”
Section: Case Presentationmentioning
confidence: 99%